Law and economic development: current issues - Batievskaia V. B., Kelekhsaeva M. V., Sitokhova T. E., Minakov A. V., Kruglov V. N., Kiselev A. A., Borovkova V. A., Borovkova V. A., Zolotareva I. V., Airikh G. E., Kurov A. E., Lykova O. A., Siziakina M. S., Soldatova L. I., Shmidt I. I., Shaibakova L. F., Chechulina O. A., Belostotskaia A. A., Shchankina L. N., Garnaia ivanova I. A., Serebrennikova A. V., Burtseva E. V., Medvedeva S. V. (Law and economic development: current issues, 2023)
the chapter is devoted to the study of the status and activities of the Collective Security Treaty Organization (CSTO) as a special form of interstate integration, the main purpose of which is to ensure security in the territories of the member countries of the Commonwealth of Independent States (CIS): the formation and goals of the CSTO activities are covered, the main stages of military-political transformations within the CSTO are considered, the regulatory and legal foundations of interstate interaction in this structure are studied; analysis of its effectiveness as an institute of regional security was carried out, significant problems and development prospects were identified. Among the current threats and challenges in the sphere of attention of the CSTO are illegal migration, drug and arms trafficking, transnational crime, and information security. Acute questions are also the Ukrainian crisis and the construction of a paradigm of a block confrontation between the CSTO and NATO.
Keywords: интеграция; integration; сотрудничество; cooperation; международная организация; international organization; Организация Договора о коллективной безопасности; постсоветское пространство; коллективная безопасность; Collective Security Treaty Organization; post-Soviet space; collective security